An assessment of line of credit for Canadian firms: A post financial crisis evidence - Emmanuel Oyasor (New Applied Studies in Management, Economics & Accounting)
Line of Credit (LOC) is a credit source extended to firms by a bank or other financial institutions to help firms meet their short- and long-term obligations. The study’s broad aim is to examine the effect of the 2008 financial crisis on firms’ use of LOC. The study analyses the global crisis impacts on corporate financing through a LOC; examines the role of letters of credit in a firm’s liquidity management; and assesses the difficulties banks face in providing LOC facilities to firms. The study limits its scope to a few years: a year before (2007), during the crisis (2008/09), and a year after. This ensures that the gaps between the years are small and allows the study to focus on the crisis era. The paper examines 30 Canadian firms, before, during, and after the crisis, to determine whether they use more of their LOC or cash flow to finance their day-to-day financial obligations. Also, the paper intends to determine the amount of interest paid if LOCs were used by the firms. The paper finds that during the crisis, 10 Canadian firms were able to meet their day-to-day operations without relying much on LOC. They used more of their cash flow instead of LOCs to meet their financial obligations, and during the period of the crisis, the firms used less of their LOCs, which indicates that lower interest were being paid by the firms. For some firms, the difference in percentage of their cash flow usage between the year before the crisis and during the year of the crisis was not so significant. Some firms had been in the habit of always using their cash flow to meet their day-to-day financial obligations. These firms would always be in the right position to get more credit from the bank.